• Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
Loser66
  • Loser66
My question on it is: No matter what the method I use, the answers must be the same, right? method 1) directly substitute f(n-1), f(n-2) to find f(n), we get d is the final answer.
Loser66
  • Loser66
for the first question.
geerky42
  • geerky42
Well, clearly if answer is not same, then you are incorrectly using method. :P

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Loser66
  • Loser66
How about this: f(n) = -4f(n-1) -3f(n-2) We can go backward like f(n+2) = -4 f(n+1) -3f(n)
Loser66
  • Loser66
that give us the characteristic equation for recursive formula is: r^2 +4r+3 =0, \(r_1= -3 \) \(r_2= -1\) Hence the general solution for it is \(f(n) = C_1 (-3)^n +C_2(-1)^n\)
Loser66
  • Loser66
f(0) = -5, hence -5 = C1 + C2 f(1) = 20 , hece 20 = -3C1-C2 solve them, it gives me C1 = -15/2 C2 = 5/2
Nnesha
  • Nnesha
yes d is correct .... .-. \[\rm f(2) = -4•f(2 -1) - 3•f(2 - 2) \]\[\rm f(2) = -4•f(1) - 3•f(0) \] =-65 :-)???
geerky42
  • geerky42
@Nnesha Loser66 is more of looking for a way to find explicit formula.
Nnesha
  • Nnesha
otay.
Loser66
  • Loser66
oh, I know my mistake. hihihi. it works well just the way I count f(3) is f(2) in the sequence. hehehe.. Thanks you all.
Loser66
  • Loser66
@Nnesha my goal is to apply my knowledge in Discrete Math to put it in logic
Nnesha
  • Nnesha
otay. http://prntscr.com/7fakty
Loser66
  • Loser66
\(f(n) = \dfrac{5}{2}(-1)^n-\dfrac{15}{2} (-3)^n\) f(2) , that is n = 2 , \(f(2) = \dfrac{5}{2} -\dfrac{15}{2}*9= 65\) f(3) , that is n =3 , \(f(3) = \dfrac{5}{2}(-1)^3 -\dfrac{15}{2}(-3)^3=200\)
Loser66
  • Loser66
oh, f(2) = -65 :)
Loser66
  • Loser66
the first term is f(0) , next is f(1),
Loser66
  • Loser66
That was my mistake. hehehe...
Nnesha
  • Nnesha
gO_OD job! @Loser66 ;-)
Loser66
  • Loser66
haaaaaaaaaaaaaahahaha... thank you for the tough flower. @Nnesha
Nnesha
  • Nnesha
flower or chocolates ? Yw

Looking for something else?

Not the answer you are looking for? Search for more explanations.